Generating hope in pastoral care through relationships - Steyn, Tobias H. (HTS teologiese studies, 2012)
This article concerned itself with the notion of Christian hope, in the midst of suffering, where this hope will find its energy from within a relationship with God and his people. Hope in God finds its substance from our past, our present and our future relationship with God. Because of this relationship, Christian hope urges caregivers and care seekers into action, enabling them to resist evil and bringing liberation in suffering.